The Relationship Between Hospital Image and Patient Satisfaction at Wiyung Sejahtera Hospital Surabaya - Al Fahira, Syalwa Khana; Wartiningsih, Minarni; Santoso, Jemima Lewi; Yuwono, Natalia (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Abstract Background: A hospital with a good reputation will influence the thoughts and behavior of the public or patients toward it. In addition to providing a competitive advantage for the hospital, a good reputation can increase patient satisfaction, service quality, competitiveness, morale, patient loyalty, and willingness to return. The purpose of this study was to analyze the relationship between hospital image and patient satisfaction level of Wiyung Sejahtera Hospital Surabaya. Method: This study used an observational quantitative methodology with the application of analytical observation. Cross-sectional design with a sample of 99 outpatients at Wiyung Sejahtera Hospital Surabaya selected by simple random sampling in August to October 2024. The dependent variable was related to outpatients' satisfaction at Wiyung Sejahtera Hospital Surabaya. The independent variable was associated with the hospital's image towards outpatients at Wiyung Sejahtera Hospital Surabaya. Univariate and bivariate analysis using Spearman correlation. Results: The results of bivariate analysis with the Spearman correlation test show that hospital image variables have a significant relationship with patient satisfaction (p = 0.000, p < 0.050), hospital personality variables have a significant relationship with patient satisfaction (p = 0.000, p < 0.368), hospital association variables have a significant relationship with patient satisfaction (p = 0.000, p < 0.431), hospital attitudes-behaviors variables have a significant relationship with patient satisfaction (p = 0.000, p < 0.492), benefits and advantages of hospital variables have a significant relationship with patient satisfaction (p = 0.000, p < 0.577). Conclusion: There is a significant relationship between hospital image variables and patient satisfaction at Wiyung Sejahtera Hospital Surabaya.